Participation of students in University Governance: A case of Mwenge Catholic University, Tanzania - Lyamtane, Rev. Eugene; Ogoti, Evans (International Journal of Scientific Research and Management (IJSRM), 2018)
This study focused on participation of students in University governance.  Specifically it was anchored on shared governance principle to interrogate the levels of student’s participation, with the view to understanding the extent to which students, as major stakeholders, have been mainstreamed in the democratization of governance in Mwenge Catholic University. Utilizing the convergent parallel design.to collect both qualitative and quantitative data, merge the data and use the results to understand the research problem. Both probability and non-probability sampling techniques were used. Data was collected from 84 students, three deans of faculties, one director and two University administrators. The study concluded that Mwenge Catholic University recognize, both in principle and practice, the importance of students’ participation in governance processes and that the nature and level of  participation of students in the governance processes in  the University has been articulated and students attach high importance in their inclusion in various governance structures.  The study recommends that a paradigm shift should occur in the University, concerning the handling of students’ involvement and participation in the governance process and the university should formulate specific strategies for the nurturing and entrenching of a democratic and participative culture among students as well as among all cadre of management staff.